The Impact of the Financial Crisis on Poverty and Income Distribution in Mongolia - World Bank (World Bank, Washington, DC, 2017)
The financial crisis of 2008-09 has considerably slowed the pace of economic growth in Mongolia. When combined with the Dzud (severe winter storm) of 2009-10, which occurred just as the economy was beginning to recover and killed over one million heads of livestock, the slowdown is likely to have significant impacts on poverty as well as the distribution of income and consumption among the poor and non-poor. In this paper we examine the poverty and distributional impacts of the crisis in Mongolia, relying on predictions from a simulation model based on pre-crisis data, given that household data to measure impacts during and after the crisis is unavailable. It is difficult to predict the distributional impacts of the financial crisis with a high degree of confidence. Evidence from previous crises suggests that relative inequality falls about as often as it rises during aggregate contractions (Paci et al, 2008). Furthermore, as the crisis spreads within a country (through adjustments in domestic credit and labor markets and fiscal policies), its impacts across different groups, sectors or areas became all the more difficult to track. The paper is structured as follows. Section two outlines the basic methodological approach used to create the simulation results used here. Section three discusses the macroeconomic projections that are used as inputs into the model. Sections four and five examine the model's projections for poverty and distributional impacts respectively, section six discusses the impact of Dzud (severe winter) and section seven concludes.